Students’ Digital Literacy Skill at Universitas PGRI Palembang - Diani, Oktrianti; Amiruddin, Amiruddin (Yayasan Sembilan Pemuda Indonesia, 2023)
Developing digital literacy skills is necessary for students to survive in industrial revolution 4.0. The objective of this study aimed to find out the digital literacy skills of students in the English Education Study Program at Universitas PGRI Palembang. The sample of this study were 25 students enrolled in the second semester of the English education study program at Universitas PGRI Palembang. The survey used a Likert scale to score responses, with Strongly Disagree (SDA) equaling 1, Disagree (DA) equaling 2, Agree (A) equaling 3, and Strongly Agree (SA) equaling 4. Every single statement in the questionnaire was related to the data collected by percentage analysis. Based on The results of data analysis indicated that students of English Education Study Program at University of PGRI Palembang have digital literacy skill. They can use and utilize technology in their daily lives.